2010
DOI: 10.1111/j.1447-0756.2010.01180.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a heterotopic tubal pregnancy by gasless laparoscopic surgery

Abstract: Heterotopic pregnancy is a rare event and management is by either laparotomy or laparoscopic surgery to remove the extrauterine pregnancy. As there has been no report detailing the use of gasless laparoscopy for management of heterotopic pregnancy, the authors herein report a case of heterotopic pregnancy that was successfully managed by gasless laparoscopic surgery. The subsequent antenatal course was unremarkable. The intrauterine pregnancy carried to term with uneventful maternal and fetal outcomes. Thus, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(44 reference statements)
0
5
0
5
Order By: Relevance
“…16,17 La tasa de detección ultrasonográfica de embarazo heterotópico en mujeres asintomáticas es del 15,8% y puede variar desde 41 hasta 84% en mujeres con dolor pélvico. 9,19,20 El pronóstico del embarazo intrauterino depende de la precocidad del diagnóstico clínico y ecográfico. 5,13 El objet ivo pr incipal en el manejo de est a patolog ía es ter m i na r el emba ra z o extrauterino sin afectar la gestación intrauterina v iable.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…16,17 La tasa de detección ultrasonográfica de embarazo heterotópico en mujeres asintomáticas es del 15,8% y puede variar desde 41 hasta 84% en mujeres con dolor pélvico. 9,19,20 El pronóstico del embarazo intrauterino depende de la precocidad del diagnóstico clínico y ecográfico. 5,13 El objet ivo pr incipal en el manejo de est a patolog ía es ter m i na r el emba ra z o extrauterino sin afectar la gestación intrauterina v iable.…”
Section: Discussionunclassified
“…5,13 El objet ivo pr incipal en el manejo de est a patolog ía es ter m i na r el emba ra z o extrauterino sin afectar la gestación intrauterina v iable. 6,7,9,18,20,21 El ma nejo del emba ra zo heterotópico cuenta con varias opciones, incluyendo conducta expectante, inyección guiada por ultrasonido de cloruro de potasio o metotrexate, salpingostomía o salpingectomía abierta o por laparoscopia. 12,13,22 Acerca del manejo con inyección de sustancias hipertónicas o metotrexate en el embrión extrauterino, la seguridad para el embarazo intrauterino no está clara.…”
Section: Discussionunclassified
“…20 A recent report found the recurrence rate of gasless laparoscopy myomectomy was 11.7% after 1 year, 36.1% after 3 years, 52.9% after 5 years and 84.4% after 8 years. 16 Fauconnier et al 21 reported a higher recurrence rate with laparoscopic surgery compared with laparotomy. The relatively high recurrence rate of traditional laparoscopic surgery is primarily a consequence of the omission of small uterine myomas due to inability to palpate the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Gasless laparoscopic surgery uses an abdominal-wall lift system to provide surgical space and a clear intra-abdominal view. 16 Because there is no need for artificial pneumoperitoneum, concerns regarding loss of insufflation and the visibility of surgical field are negated. Gasless laparoscopy allows the use of more reliable instruments and techniques, compared with conventional laparoscopy 6,7 and has, therefore, gained popularity among gynaecologists.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of the use of CO 2 laparoscopy in the management of heterotopic pregnancy [22,23]. More recently, the first case of heterotopic tubal pregnancy treated using GLS has been reported [24]. The woman was successfully managed under general anesthesia at the seventh week of gestation using GLS salpingectomy of the tubal pregnancy.…”
Section: Gynecologic Proceduresmentioning
confidence: 99%